Health Facilities Readiness and Determinants to Manage Cardiovascular Disease in Afghanistan, Bangladesh, and Nepal: Evidence from the National Service Provision Assessment Survey - Md. Durrul Huda; Mosiur Rahman; Md. Golam Mostofa; Prosannajid Sarkar; Md. Jahirul Islam; Izzeldin Fadl Adam; Nguyen Huu Chau Duc; Saber Al-Sobaihi (Ubiquity Press, 2024)
Background: In South Asia, cardiovascular diseases (CVDs) are an increasing public health concern. One strategy for dealing with the growing CVDs epidemic is to make health facilities more ready to provide CVDs services. The study's objectives were to: (1) assess healthcare facilities' readiness to offer CVDs services; and (2) identify the variables that influence such readiness. Methods: This study employed data from the Afghanistan Service Provision Assessment Survey 2018-2019, Bangladesh Health Facility Survey 2017, and Nepal Health Facility Survey 2021 that were cross-sectional and nationally representative. In Afghanistan, Bangladesh, and Nepal, 117, 368, and 1,381 health facilities, respectively, were examined. A total of 10 items/indicators were used to measure a health facility's readiness to provide CVDs services across three domains. Results: The mean readiness scores of managing CVDs were 6.7, 5.6, and 4.6 in Afghanistan, Bangladesh, and Nepal, respectively. Availability of trained staff for CVD services are not commonly accessible in Afghanistan (21.5%), Bangladesh (15.3%), or Nepal (12.9%), except from supplies and equipment. Afghanistan has the highest levels of medicine and other commodity availability. Among the common factors linked with readiness scores, we ought to expect a 0.02 unit rise in readiness scores for three nations for every unit increase in number of CVDs care providers. In Afghanistan, Bangladesh, and Nepal, availability of both diagnosis and treatment facilities was associated with increases in readiness scores of 27%, 9%, and 17%, respectively. Additionally, an association was observed between nation-specific facility types and the readiness scores. Conclusions: Country-specific factors as well as universal factors present in all three nations must be addressed to improve a health facility's readiness to provide CVDs care. To create focused and efficient country-specific plans to raise the standard of CVD care in South Asia, more investigation is necessary to ascertain the reasons behind country-level variations in the availability of tracer items.